PERBEDAAN KELELAHAN DAN STRES KERJA PADA TENAGA KERJA SHIFT I, II DAN III BAGIAN PRODUKSI PABRIK MINUMAN PT. X SEMARANG - Melcy Novitasari; Siswi Jayanti; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Abstract : Shift work is one of the company’s strategies to maximaze company’s productivity and efficiency. Meanwhile, this strategy had several problems specially for employees who can or less adapt to the working hours. Problems that may arise is the fatigue and job stress. This study aimed at investigated the difference between fatigue and job stress of production workers shift I, II and III the beverages factory PT. X Semarang. This research is analytic survey with cross sectional approach. Samples used were 42 workers, who worked on shift I, II and III. Measurement of fatigue by used Bourdon Wiersma test to see results of speed, accuracy and constancy, and for job stress used General Health Questionnaire 12 (GHQ-12). Analysis used Oneway Anova Test. The results of fatigue, there are differences speed and accuracy before and after work between shift I, II and III (p value = 0,000); differences constancy before work between shift I, II and III (p value = 0,001); there is no difference constancy after work between shift I, II and III (p value = 0,870). Results of measurements job stress, there were differences job stress between shift I, II and III (p value = 0,008). From this study it can be concluded, there were differences fatigue in terms of speed, accuracy and constancy and job stress between shift I, II and III.